The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1051/animres:2006007
|View full text |Cite
|
Sign up to set email alerts
|

Less intensified grazing management with growing fattening bulls

Abstract: -Animal performance, composition and quality of meat from Belgian Blue bulls either fattened indoors (FI) or finished indoors after a previous grazing period were studied during six years. During the grazing period, three intensification managements were tested on a permanent pasture conducted as set stocking. The intensification levels were either high (HN: 140 kg N·ha −1 with 6 bulls·ha −1 ) or moderate with a 33% reduction of nitrogen fertilisation but with the same stocking rate (MN: 93 kg N·ha −1 , 6 bull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 26 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The N-use efficiency (N output input − 1 ha − 1 ) for Systems HH2, HL2, LL2 and LL1 were 0.11, 0.16, 0.16 and 0.17, respectively. Dieguez Cameroni et al (2006) reported an apparent N efficiency of 0.13, 0.15 and 0.26 during the grazing period for growing fattening bulls on high N-high SR, moderate N-high SR and zero N-low SR systems, respectively. From a review of the literature Peyraud and Astigarraga (1998) concluded that lowering levels of N fertilisation (with an appropriate reduction in SR) appeared to be an effective means of reducing N losses of ruminants in grazing systems with little or no change in the animals nutrition or in their individual output.…”
Section: Liveweight Output and Nitrogen Balance Hectare −mentioning
confidence: 99%
“…The N-use efficiency (N output input − 1 ha − 1 ) for Systems HH2, HL2, LL2 and LL1 were 0.11, 0.16, 0.16 and 0.17, respectively. Dieguez Cameroni et al (2006) reported an apparent N efficiency of 0.13, 0.15 and 0.26 during the grazing period for growing fattening bulls on high N-high SR, moderate N-high SR and zero N-low SR systems, respectively. From a review of the literature Peyraud and Astigarraga (1998) concluded that lowering levels of N fertilisation (with an appropriate reduction in SR) appeared to be an effective means of reducing N losses of ruminants in grazing systems with little or no change in the animals nutrition or in their individual output.…”
Section: Liveweight Output and Nitrogen Balance Hectare −mentioning
confidence: 99%
“…The differences in performance during the housing period between Control bulls and both groups of steers could be attributed to the different energy and protein content of diets. Including forage in the beef diets reduces average daily [page 867] gain and feed efficiency (Dieguez Cameroni et al, 2006;Patterson et al, 2000), depending on the proportion forage:concentrate (Nuernberg et al, 2005) mainly due to the lower energy concentration of forages. Furthermore, the different gender could enlarge the differences in weight gains because it affects both intake and feed efficiency for growth (Andersen and Ingvartsen, 1984).…”
Section: Live Weight Weight Gains and Intakementioning
confidence: 99%